2019
DOI: 10.1371/journal.pcbi.1007051
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of surgical intervention outside the epileptogenic zone in the Virtual Epileptic Patient (VEP)

Abstract: Studies to improve the efficacy of epilepsy surgery have focused on better refining the localization of the epileptogenic zone (EZ) with the aim of effectively resecting it. However, in a considerable number of patients, EZs are distributed across multiple brain regions and may involve eloquent areas that cannot be removed due to the risk of neurological complications. There is a clear need for developing alternative approaches to induce seizure relief, but minimal impact on normal brain functions. Here, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 80 publications
(108 reference statements)
0
73
0
Order By: Relevance
“…The demonstration of a sizeable contribution of cerebro-cerebellar connectivity to global brain dynamics suggests that TVB has the potential to reveal the impact of specific subnetworks on global brain dynamics and to understand the interaction of multiple brain areas ( Aerts et al, 2018 ; Zimmermann et al, 2018 ; An et al, 2019 ). A further improvement to TVB performance could be achieved by using multimodal datasets merging MRI, EEG, MEG, positron emission tomography (PET) data ( Schirner et al, 2018 ; Stefanovski et al, 2019 ; Triebkorn et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration of a sizeable contribution of cerebro-cerebellar connectivity to global brain dynamics suggests that TVB has the potential to reveal the impact of specific subnetworks on global brain dynamics and to understand the interaction of multiple brain areas ( Aerts et al, 2018 ; Zimmermann et al, 2018 ; An et al, 2019 ). A further improvement to TVB performance could be achieved by using multimodal datasets merging MRI, EEG, MEG, positron emission tomography (PET) data ( Schirner et al, 2018 ; Stefanovski et al, 2019 ; Triebkorn et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have demonstrated the potential of TVB to investigate physiological brain states not only in healthy subjects ( Schirner et al, 2018 ) but also in neurological diseases. For example, in tumors and epilepsy TVB has been used to predict the surgical outcome, while in Alzheimer’s disease has been used to predict neurodegenerative progression ( Aerts et al, 2018 , 2020 ; Zimmermann et al, 2018 ; An et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 89 90 The VEP model was constructed based on Epileptor, 103 , 104 a phenomenological neural mass model replicating seizure characteristics, and patient-specific features including brain connectivity and magnetic resonance imaging lesions, and fit and validated using the individual sEEG recordings. 98 , 99 Based on this personalized modeling approach, Jirsa’s group has been conducting successive studies in various directions for clinical applications, such as inference of the epileptogenicity of the brain regions, 102 analysis of the seizure propagation characteristics, 99 101 and prognostic prediction of the surgical Intervention. 100 , 101 …”
Section: Patient-specific Whole-brain Modelsmentioning
confidence: 99%
“… 98 , 99 Based on this personalized modeling approach, Jirsa’s group has been conducting successive studies in various directions for clinical applications, such as inference of the epileptogenicity of the brain regions, 102 analysis of the seizure propagation characteristics, 99 101 and prognostic prediction of the surgical Intervention. 100 , 101 …”
Section: Patient-specific Whole-brain Modelsmentioning
confidence: 99%
See 1 more Smart Citation